2018
DOI: 10.33582/2637-8027/1002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of omega-3 fatty acids on offending behavior in repeat violent offenders: A randomized controlled trial feasibility study

Abstract: Evidence suggests that certain behavioral problems, including a tendency towards impulsive-violence, might arise in part as a consequence of a potentially correctable, dietary imbalance of essential fatty acids in susceptible individuals. This study aimed to determine the feasibility of conducting a Randomized Controlled Trial (RCT) using omega-3 polyunsaturated fatty acid supplementation in a community sample of impulsive, repeat-violent offenders. Behavioral measures of impulsivity, anger, depression, irrita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The Omega-3 Index is emerging as a risk factor for mental health, with low levels associated with depression and schizophrenia [17] and people at ultra-high risk of psychosis [18]. We previously reported a negative correlation between the Omega-3 Index and aggressive behaviour in Australian prisoners [19], while Miles et al [20] reported that violent offenders released into the community and provided 3 g of n-3 LCPUFA daily had an increased Omega-3 Index and reduced post-release criminal behaviour. Thus, the evidence to date would suggest that the Omega-3 Index is a useful biometric to evaluate the efficacy of omega-3 supplementation in people with aggressive behaviour.…”
Section: Introductionmentioning
confidence: 84%
“…The Omega-3 Index is emerging as a risk factor for mental health, with low levels associated with depression and schizophrenia [17] and people at ultra-high risk of psychosis [18]. We previously reported a negative correlation between the Omega-3 Index and aggressive behaviour in Australian prisoners [19], while Miles et al [20] reported that violent offenders released into the community and provided 3 g of n-3 LCPUFA daily had an increased Omega-3 Index and reduced post-release criminal behaviour. Thus, the evidence to date would suggest that the Omega-3 Index is a useful biometric to evaluate the efficacy of omega-3 supplementation in people with aggressive behaviour.…”
Section: Introductionmentioning
confidence: 84%
“…Some research specifically investigated the effects of omega‐3s on violent offenders. In one experiment, repeat violent offenders with high impulsivity were given omega‐3 supplementation or a placebo (Miles et al., 2018). At the end of the 12‐week trial, there was no main effect of supplementation; however, a blood analysis revealed that offenders with higher omega‐3 concentrations were less likely to have committed a crime during the study.…”
Section: Part Ii: Breaking the Cycle Of Punishment And Violence Via Nmentioning
confidence: 99%
“…In an RCT on a general population sample, authors of one study found a significant decrease in self‐reported aggression ( p = .032, d = 0.31) after omega‐3 fatty acid supplementation (Bègue et al, 2018). In the other excluded study (Miles et al, 2018), an RCT of community‐based individuals with histories of violent offending, the authors found no significant effect of omega‐3 fatty acid supplementation on self‐reported re‐offending ( p = .074; neither effect size, nor direction of change was reported and related follow‐up questions to the original study authors remained unanswered).…”
mentioning
confidence: 96%